Pengaruh media pembelajaran mobile learning materi mempertahankan kemerdekaan Indonesia di Kabupaten Lamongan 1948-1949 terhadap kemampuan pemahaman sejarah lokal siswa kelas XI MAN 1 Lamongan - Ahmadi, Ishom; Sapto, Ari; Leksana, Grace Tjandra (Historiography: Journal of Indonesian History and Education, 2024)
Abstract The article aims to identify the impact of the application of mobile learning media on the history of defending Indonesian independence in Lamongan Regency 1948-1949 on the understanding of local history of class XI students at MAN 1 Lamongan. This research uses a quantitative method with an experimental study approach, and the design used is One Group Pretest-Posttest, by measuring the results of the pretest before treatment and posttest after treatment. The study population was the XI grade students of MAN 1 Lamongan, while the sample consisted of 36 students of class XI IPS 1 who had studied this material. This study used cluster sampling technique and data analysis with paired sample t-test and met the prerequisite test with Shapiro-Wilk method. The results showed an increase in understanding of local history, which was reflected in the pretest of 63.89 and posttest of 80.69. Hypothesis testing showed a significance value (2-tailed) of 0.000